2019
DOI: 10.1038/s42255-019-0033-z
|View full text |Cite|
|
Sign up to set email alerts
|

Olfaction regulates organismal proteostasis and longevity via microRNA-dependent signalling

Abstract: Introductory The maintenance of proteostasis is crucial for any organism to survive and reproduce in an ever-changing environment, but its efficiency declines with age1. Posttranscriptional regulators such as microRNAs control protein translation of target mRNAs with major consequences for development, physiology, and longevity2,3. Here we show that food odor stimulates organismal proteostasis and promotes longevity in Caenorhabditis elegans through mir-71-mediated inhibition of tir-1 mRNA stability in olfacto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 60 publications
0
49
0
Order By: Relevance
“…Olfactory sensation plays crucial roles in regulating organism fitness and survival. AWA and AWC olfactory neurons are known to regulate organism lifespan 46 , AWB olfactory neurons modulate reproductive longevity in response to microbial inputs 47 , and more recently, AWC olfactory neurons are linked to the proteostasis control in peripheral tissues 48 . Here, our studies discover that olfactory perception through AWC neurons also actively regulates peripheral adiposity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfactory sensation plays crucial roles in regulating organism fitness and survival. AWA and AWC olfactory neurons are known to regulate organism lifespan 46 , AWB olfactory neurons modulate reproductive longevity in response to microbial inputs 47 , and more recently, AWC olfactory neurons are linked to the proteostasis control in peripheral tissues 48 . Here, our studies discover that olfactory perception through AWC neurons also actively regulates peripheral adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 2-butanone affects bacterial motility and biofilm formation 53 , and thus may also serve as a signal associated with bacterial stress to modulate fat storage dynamics in the host. Recent studies have shown that AWC neurons regulate peripheral proteostasis in response to bacterial odors, and discovered specific NLP neuropeptides involved in this regulation 48 . For this olfactory regulation, it remains unclear the NATURE COMMUNICATIONS | https://doi.org/10.1038/s41467-020-15296-8 ARTICLE neural circuit and peripheral factors that transduce signals from AWC neurons to regulate proteostasis.…”
Section: Discussionmentioning
confidence: 99%
“…This neuron-to-gut communication is governed by the microRNA miR-71, which controls the level of the Toll-receptor-domain protein TIR-1 in AWC neurons. Thus, disruption of miR-71-tir-1 or loss of AWC olfactory neurons eliminates the influence of food source on chemotactic behavior and proteostasis (Finger et al 2019). Showing that a neuronal olfactory circuit rewires Figure 3 Organismal coordination of proteostasis networks.…”
Section: Organismal Regulation Of Stress Response and Proteostasismentioning
confidence: 99%
“…The nature of imperfect binding specificity means that a single miRNA can regulate a large number of mRNA targets involved in complex cellular processes, thereby tightly controlling genetic networks during development and in response to stress (Pocock, 2011). As such, dysregulation of miRNA-controlled processes can cause severe physiological consequences for animal behavior and survival (Boulias and Horvitz, 2012; de Lencastre et al, 2010; Finger et al, 2019; Grueter et al, 2012; Kagias and Pocock, 2015; Nehammer et al, 2015; Vora et al, 2013). In addition, due to their rapid and reversible regulatory capacity, miRNAs are prime candidate facilitators of responses to proteotoxic stress.…”
Section: Introductionmentioning
confidence: 99%